Oyster Care: An Innovative Palliative Approach towards SPMI Patients - Decorte, Ilse; Verfaillie, Françoise; Moureau, Loïc; Meynendonckx, Sandrine; Van Ballaer, Kim; De Geest, Isabelle; Liégeois, Axel (Frontiers in Psychiatry, 2020)
Oyster Care is the result of the search by caregivers in Flanders, Belgium, to develop quality care for patients with a Severe and Persistent Mental Illness (SPMI). This article offers a conceptual analysis of the Oyster Care model, based on a brief review of specialist literature and several cases. The starting point of the development of this new care model is the complex and difficult context of the care for SPMI patients. Their needs and suffering are very challenging on account of a wide variety of causes. At the same time they are in danger of being neglected by the care system. Paradoxically, the development and implementation of psychosocial rehabilitation in Belgian mental health care puts the care for these patients under pressure. In practice, they are often exposed to over- or under-treatment. Oyster Care is an innovative form of the palliative approach and philosophy, tailored to the specific target group of SPMI patients. It is based on four pillars: physical care adequately responding to the somatic impairments of these patients; psychological care changing the scope of therapy by focusing on mental comfort and rest; social care providing a structure of daily activities and contacts; existential care enhancing the experience of life as valuable and meaningful. The wellbeing of patients is paramount and requires a range of interventions, such as a highly personal approach, a flexible approach to rules, a great dose of creativity in everyday life, extensive expertise in somatic care, and specific attention to existential needs and the search for meaning. The development of this care model in a number of care units in Flanders increases the wellbeing of the patients and creates a significant positive dynamic among caregivers. However, more research and resources are needed to further develop and integrate this model. An instrument to measure the evolution of the wellbeing of SPMI patients would be very helpful for caregivers.